취리히 종교개혁에 나타난 츠빙글리의 사회개혁 사상 - 김유준(KIM You-Joon) (Changsin nondan, 2024)
츠빙글리의 종교개혁은 단순히 교회개혁에 머물지 않았고 사회 전반에 걸친 사회개혁으로 구체화 되었다. 이에 본 연구는 취리히 종교개혁에 나타난 츠빙글리의 사회개혁 사상에 초점을 두고 분석하고자 한다. 츠빙글리는 일확천금에 대한 경계를 강조하며, 하나님의 영광과 이웃의 유익을 위한 신성한 노동의 중요성을 강조했다. 그는 교회개혁과 더불어 시의회 의원으로서 사회복지 정책 및 제도적 차원의 사회개혁을 적극적으로 추진하였다. 이러한 과정에서 츠빙글리는 종교적 신념과 사회적 책임을 결합하여, 교회와 사회가 상호 작용할 수 있는 모델을 제시하였다. 또한 그는 하나님의 절대적 정의를 강조하며 인간의 정의를 상대화하고, 생명을 위한 복지와 섬김의 사회개혁 사상을 구체화하였다. 이러한 츠빙글리의 사회개혁 사상은 여러 중요한 측면에서 현대사회에 시사점을 제공한다. 첫째, 그는 현대사회의 경제적 양극화 문제에 대한 비판적 시각을 제공하며, 기존의 불의한 경제체제의 절대화를 거부하는 근거를 마련해 주었다. 둘째, 그의 사상은 교회개혁과 함께 사회 전반에 걸친 개혁의 통찰력을 제시하며, 종교와 사회의 관계를 재조명하는 기회를 제공해 주었다. 셋째, 츠빙글리의 사상은 희년 사상에 기초하여 인간의 기본권 보장과 약자 보호, 생명 존중 및 친환경적 경제활동의 기초를 형성하는 토대를 마련해 주었다. 이러한 측면에서 츠빙글리의 사회개혁 사상은 현대사회의 다양한 문제에 대한 해결책을 모색하는 데 중요한 통찰력과 사상적 토대를 제시해 주었다. Zwingli’s Reformation extended beyond church reform into a comprehensive social movement that transformed the entire society. This study analyzes Zwingli’s social reform ideas as manifested in the Zürich Reformation. He warned against pursuing quick wealth while emphasizing the importance of sacred labor for God’s glory and neighbors’ welfare. As a city council member, Zwingli not only pursued ecclesiastical reforms but also championed social welfare policies and institutional changes. Through these efforts, he bridged religious beliefs with social responsibility, creating a model for church-society interaction. His vision centered on God’s absolute justice, putting human concepts of justice in perspective, while advocating for social reforms focused on welfare and life-affirming service. Zwingli’s social reform ideas remain relevant to modern society. He offered keen insights into economic inequality, creating a basis for challenging unjust economic systems. His integration of church and societal reform provides valuable lessons for understanding religion’s role in society. Drawing from the concept of Jubilee, his ideas established principles for human rights, protection of vulnerable populations, respect for life, and sustainable economic practices. Thus, Zwingli’s social reform philosophy continues to provide crucial insights for addressing contemporary social challenges. KCI Citation Count: 0